Drilling fluid for well wall of fracture zone as well as preparation method and application of drilling fluid

By using prehydrated bentonite and a combination of multiple anti-collapse agents in the drilling fluid, sodium-based bentonite is formed, combining components such as sulfonated drilling fluid system and API barite, the stability and high well walls of ultra-deep well fault zones are solved. The problem of density rheology performance achieves the stability and sealing effect of well wall at high temperature of 160℃, and improves drilling efficiency.

CN119220230APending Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310790331.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing drilling fluid has insufficient stability in the crushed formation in the ultra-deep well fault zone, and the rheology performance is difficult to control at high density, especially instability at high temperatures of 160℃, affecting drilling efficiency.

Method used

A drilling fluid system is adopted, including water, bentonite, filtration loss reducer, inhibitor, anti-collapse agent, soda ash and weighting agent. By prehydrated bentonite, it is evenly mixed with other components to form sodium-based bentonite, combining different particle sizes. The anti-collapse agent and sulfonated drilling fluid system with the mechanism of action, uses API barite and submicron barite as weighting agents to adjust density and sealing effect.

Benefits of technology

Maintain good rheology at high temperature of 160℃, effectively seal the micropore joints of the formation surrounding wells, and maintain the stability of the well wall to the greatest extent, overcoming the insufficient stability of the well wall of conventional water-based drilling fluid and the difficulty in controlling the rheology performance under high density. Problem, improving drilling efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004313411310000021
    Figure BDA0004313411310000021
  • Figure BDA0004313411310000031
    Figure BDA0004313411310000031
  • Figure BDA0004313411310000032
    Figure BDA0004313411310000032
Patent Text Reader

Abstract

The invention provides drilling fluid for a well wall of a fracture zone as well as a preparation method and application of the drilling fluid. The drilling fluid comprises water, bentonite, a filtrate reducer, an inhibitor, an anti-collapse agent, sodium carbonate, caustic soda, a dispersing agent and a weighting agent, the preparation method comprises the following steps: pre-hydrating the bentonite, and uniformly mixing the pre-hydrated bentonite with the filtrate reducer, the inhibitor, the anti-collapse agent, the caustic soda, the dispersing agent and the weighting agent to obtain the drilling fluid. The drilling fluid disclosed by the invention can be applied to drilling of fracture zone fractured formations of ultra-deep wells and extra-deep wells along north, can resist high temperature of 160 DEG C, can keep good rheological property in a high-density state of 1.6-2.0 g / cm < 3 >, can effectively carry rocks and quickly block formation micro-pores around wells at the same time, and can keep the stability of well walls to the greatest extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of drilling fluid, and more particularly to a drilling fluid for a broken zone well wall and a preparation method and application thereof. Background Art

[0002] The broken strata in the fault zone are one of the complex strata for oil and gas drilling, and the instability of the wellbore seriously affects the exploration and development process. The notable characteristics of the broken strata are fragmentation, incompleteness, poor cementation, crack development and uneven distribution of ground stress, which can easily lead to complex accidents such as wellbore collapse, block drop and drill bit jam. Affected by the structure of the fault zone, some of the Yijianfang Formation and Yingshan Formation formations of the Ordovician System in Shunbei Oil and Gas Field are highly fragmented and poorly cemented, resulting in drilling accidents such as collapse and block drop, resulting in huge losses in economic and social benefits.

[0003] The reservoir types of Yijianfang Formation and Yingshan Formation in Shunbei Oil and Gas Field are mainly fracture type and fracture-cavern type. The formation of reservoirs is mainly affected by the fracture system and fluid properties, sources and scale. The fracture system directly controls the development of fracture reservoirs, which can improve the permeability of reservoirs and provide channels for the injection of fluids or oil and gas. It is the main controlling factor for the development of reservoirs. An in-depth analysis of the mechanism of wellbore instability in fractured formations in fault zones shows that, in terms of drilling fluid technology, there are mainly the following coping strategies: (1) Strengthen plugging and film formation to reduce the tendency of drilling fluid filtrate to enter microcracks; (2) Improve the surface properties of clay minerals, transform their hydrophilicity into hydrophobicity, and reduce their surface hydration capacity; (3) Improve the cementation and anti-collapse capacity of broken formations; (4) Optimize the appropriate drilling fluid density; (5) Maintain excellent rheology and improve the rock carrying effect.

[0004] Patent CN104910879A describes an anti-collapse drilling fluid, which contains the following components: potassium polyacrylate, anti-collapse inhibitor (polyacrylamide, epoxypropyltrimethylammonium chloride, potassium chloride, polyquaternary ammonium salt and water). Patent CN104177517A describes a bionic polymer for well wall stabilization, its preparation method and drilling fluid. The polymer contains carboxymethyl chitosan as the main chain and a group derived from dopamine grafted on the main chain, which can improve the strength of the mud shale on the well wall, seal the pores of the mud shale on the well wall and reduce the filtration loss of the drilling fluid, thereby stabilizing the well wall of the mud shale formation during the drilling process. However, the temperature resistance of the above two anti-collapse drilling fluids is less than 150°C, and high temperature and high density can easily lead to system instability, affecting drilling construction.

[0005] Therefore, a drilling fluid with a stable wellbore in the fault zone was developed, which has a temperature above 160°C and a density of 1.8 to 2.0 g / cm 3 It can maintain good inhibition and rheological properties, which can effectively improve drilling efficiency. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a drilling fluid for a broken zone well wall and a preparation method and application thereof.

[0007] The purpose of the present invention is to overcome the problems of "insufficient well wall stability (anti-collapse) and high density (1.8-2.0 g / cm 3 ) The rheological properties are difficult to control" and a preparation method and application of a drilling fluid for stabilizing the wellbore in a broken zone is provided. The drilling fluid system can be used for drilling broken formations in Shunbei ultra-deep wells and ultra-deep wells in fracture zones. It can withstand high temperatures of 160°C and maintain a stable flow rate of 1.8-2.0 g / cm 3 It maintains good rheological properties under high-density conditions, effectively carries rock and quickly seals the micropores in the formation around the well, keeping the well wall stable to the greatest extent.

[0008] One of the objects of the present invention is to provide a drilling fluid.

[0009] The drilling fluid comprises water, bentonite, fluid loss reducer, inhibitor, anti-collapse agent, soda ash, caustic soda, dispersant and weighting agent;

[0010] Taking water as 100 parts by weight,

[0011]

[0012]

[0013] In a preferred embodiment of the present invention,

[0014] The bentonite is a commonly used bentonite in the prior art, such as calcium-based bentonite or sodium-based bentonite, preferably sodium-based bentonite;

[0015] The fluid loss reducer is at least one of sulfonated phenolic resin SMP, polyanionic cellulose LV-PAC, sodium carboxymethyl cellulose Na-CMC, and lignite resin;

[0016] The inhibitor is at least one of potassium chloride, polyamine, hydrolyzed polyacrylamide potassium salt, potassium humate, and polyol;

[0017] The anti-collapse agent includes a well wall strengthening agent, asphalt, a micro-nano plugging agent, a fiber material, and a sheet-like flexible bridging material;

[0018] Both soda ash and caustic soda refer to chemically pure solids;

[0019] The dispersant is at least one of sodium polyacrylate, tannin lye, and iron chromium lignin sulfonate;

[0020] The weighting agent is at least one of API barite, submicron barite, limestone powder, and hematite powder; preferably, it is a mixture of API barite and submicron barite, and more preferably, the mass ratio of API barite to submicron barite is (1.5-4):1. In addition to adjusting the density, the weighting agent also has a certain plugging effect. When the mass ratio of API barite to submicron barite is (1.5-4):1, the plugging range of the weighting agent in the present invention is larger.

[0021] In a preferred embodiment of the present invention,

[0022] The anti-collapse agent comprises the following components:

[0023]

[0024] The well wall strengthening agent, asphalt, fiber material, sheet-shaped flexible bridging material and micro-nano plugging agent are mixed, and stirred at 800 to 1600 revolutions per minute for 4 to 25 minutes to obtain the anti-collapse agent.

[0025] In a preferred embodiment of the present invention,

[0026] The well wall strengthening agent is ultrafine rigid particles, preferably at least one of ultrafine calcium carbonate, elastic graphite, limestone, sulfur ore powder, and ultrafine calcium silicate, preferably ultrafine calcium carbonate; more preferably at least one of 200 mesh, 400 mesh, 800 mesh, 1200 mesh, and 2500 mesh in particle size, most preferably more than two;

[0027] The asphalt is at least one of sulfonated asphalt, emulsified asphalt, modified sulfonated asphalt, and mineral asphalt; preferably, it is a mixture of sulfonated asphalt and emulsified asphalt, and more preferably, the mass ratio of sulfonated asphalt to emulsified asphalt is 1:(1-2.5);

[0028] The micro-nano plugging agent is at least one of nano-silicon dioxide and nano-cement, preferably with a median particle size of less than 1.0 μm, and more preferably nano-silicon dioxide;

[0029] The fiber material is at least one of polypropylene fiber, carbon fiber, cotton fiber or wood fiber, preferably polypropylene fiber;

[0030] The sheet-like flexible bridging material is at least one of mica, wood chips, and celluloid, preferably mica.

[0031] In a preferred embodiment of the present invention,

[0032] The pH of the drilling fluid is 8 to 12, preferably 9.0 to 10.0;

[0033] The drilling fluid density is 1.2 to 2.2 g / cm 3, preferably 1.6 to 2.0 g / cm 3 .

[0034] A second object of the present invention is to provide a method for preparing a drilling fluid, comprising:

[0035] The bentonite is prehydrated first, and then mixed evenly with a fluid loss reducer, an inhibitor, an anti-collapse agent, caustic soda, a dispersant and a weighting agent to obtain the drilling fluid.

[0036] In a preferred embodiment of the present invention,

[0037] (1) prehydrating bentonite to obtain a prehydrated bentonite slurry;

[0038] (2) Under stirring, the fluid loss reducer, inhibitor, anti-collapse agent, caustic soda, dispersant and weighting agent are sequentially added to the prehydrated bentonite slurry obtained in step (1) and mixed evenly.

[0039] In a preferred embodiment of the present invention,

[0040] Step (1),

[0041] Bentonite is added to water and mixed evenly under stirring, and then soda ash is added and mixed evenly to obtain a prehydrated bentonite slurry; the soda ash is added when the bentonite is prehydrated. After the soda ash is added, the sodium ions therein can convert the calcium-based bentonite into sodium-based bentonite, with a higher degree of hydration and dispersion, and calcium carbonate is precipitated to remove calcium ions; preferably,

[0042] The mixing temperature is 10 to 80°C, preferably 20 to 60°C;

[0043] The stirring rate is 800 to 1600 r / min, preferably 1000 to 1200 r / min;

[0044] The mixing time after adding bentonite is 3 to 10 minutes, preferably 5 to 8 minutes;

[0045] The mixing time after adding soda ash is 3 to 10 minutes, preferably 5 to 8 minutes;

[0046] Step (2),

[0047] The stirring rate is 800 to 1600 r / min, preferably 1000 to 1200 r / min;

[0048] Each component added in sequence should be stirred for 3 to 10 minutes, preferably 5 to 8 minutes.

[0049] The third object of the present invention is to provide a drilling fluid obtained by the above preparation method.

[0050] A fourth object of the present invention is to provide an application of a drilling fluid in oil and gas drilling in fractured formations, preferably in drilling in ultra-deep formations in fractured zones or in abnormally high-pressure well sections.

[0051] The main advantages of the fracture zone wellbore stabilization drilling fluid of the present invention compared with the prior art are:

[0052] (1) It effectively overcomes the problems of conventional water-based drilling fluids in ultra-deep and ultra-deep wells in fractured zones, such as insufficient wellbore stability (anti-collapse) and high-density conditions (1.8-2.0 g / cm 3 ) The technical problem of "difficulty in controlling rheological properties";

[0053] (2) By strengthening the sealing film formation, the tendency of drilling fluid filtrate to enter micro-cracks is effectively curbed, and the cementation and anti-collapse capacity of the broken formation is improved;

[0054] (3) It can be used in Shunbei ultra-deep wells and ultra-deep wells in broken zone formations. It can resist high temperature degradation at 160°C and maintain a temperature of 1.8-2.0g / cm 3 It maintains good rheological properties under high-density conditions, effectively carries rock and quickly seals the micropores in the formation around the well, keeping the well wall stable to the greatest extent. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0056] The raw materials used in the examples are all conventional commercially available raw materials.

[0057] Test method:

[0058] In accordance with GB / T 16783.1-2014 field test procedures for water-based drilling fluids;

[0059] Take an appropriate amount of drilling fluid, use a liquid densitometer to measure the density of the drilling fluid, use a high-temperature and high-pressure filter loss instrument to measure its high-temperature and high-pressure filter loss at 160°C and 3.5MPa, and use a steel ruler to measure the thickness of the mud cake;

[0060] The measurement conditions of high temperature and high pressure filtration loss and mud cake thickness of drilling fluid are as follows: aging at 160°C for 16 hours in a roller heating furnace, naturally cooling to room temperature, and measuring the high temperature and high pressure filtration loss and mud cake thickness of drilling fluid at 160°C.

[0061] Example 1

[0062] (1) 3 parts of ultrafine calcium carbonate (1200 mesh) and 3 parts of ultrafine calcium carbonate (2500 mesh), 3 parts of sulfonated asphalt powder, 4 parts of polypropylene fiber, 4 parts of mica and other solids, 3 parts of emulsified asphalt liquid, and 3 parts of nano silicon dioxide (median particle size less than 1.0 μm) were mixed together and stirred at 1200 rpm for 5 minutes to prepare an anti-collapse agent.

[0063] (2) Weigh 100 parts of water, then add 5 parts of sodium bentonite, stir at a rate of 1200 rpm for 5 minutes, then add 0.25 parts of soda ash, and stir at a rate of 1200 rpm for 5 minutes to prehydrate, to obtain a prehydrated bentonite slurry.

[0064] (3) Then, 3 parts of sulfonated phenolic resin as a fluid loss reducer were added to the prehydrated bentonite slurry, and 2.5 parts of lignite resin as a fluid loss reducer were added after stirring at a rate of 1200 rpm for 5 minutes, 0.7 parts of polyanionic cellulose as a fluid loss reducer were added after stirring at a rate of 1200 rpm for 5 minutes, 6 parts of potassium chloride as an inhibitor were added after stirring at a rate of 1200 rpm for 5 minutes, 0.7 parts of polyamine as an inhibitor were added after stirring at a rate of 1200 rpm for 5 minutes, and 0.6 parts of potassium chloride as an inhibitor were added after stirring at a rate of 1200 rpm for 5 minutes. After stirring at a rate of 100 rpm for 5 minutes, add the prepared anti-collapse agent, stir at a rate of 1200 rpm for 5 minutes, add 0.3 parts of sodium hydroxide to adjust the pH of the drilling fluid to 9.5, stir at a rate of 1200 rpm for 5 minutes, stir at a rate of 1200 rpm for 5 minutes, add 0.5 parts of dispersant sodium polyacrylate, add 15 parts of barite (API barite: submicron barite = 1.5:1) to adjust the density of the drilling fluid to 2.0 g / cm 3 After stirring for 5 minutes, the fracture zone wellbore stabilizing drilling fluid as described above is obtained.

[0065] Among them, the density, high temperature and high pressure filtration loss, mud cake thickness and pH measurement data of the broken zone wellbore stabilization drilling fluid are shown in Table 1.

[0066] Example 2

[0067] The differences from Example 1 are: the composition of the anti-collapse agent is different; the composition of the weighting agent is different; the density of the drilling fluid is different;

[0068] The anti-collapse agent is: 1 part of ultrafine calcium carbonate (1200 mesh) and 1 part of ultrafine calcium carbonate (2500 mesh), 1 part of sulfonated asphalt powder, 2 parts of polypropylene fiber, 2 parts of mica and other solids, mixed with 1 part of emulsified asphalt liquid and 1 part of nano silicon dioxide, and stirred at 1200 rpm for 5 minutes to prepare the anti-collapse agent;

[0069] The weighting agent is: add 7 parts of barite (API barite: submicron barite = 1.5:1) to adjust the drilling fluid density to 1.6g / cm 3 ;

[0070] Except for the above differences, other conditions of Example 2 are the same as those of Example 1.

[0071] The test results are shown in Table 1.

[0072] Example 3

[0073] The difference from Example 1 is that 3 parts of bentonite are added;

[0074] Except for the above differences, other conditions of Example 3 are the same as those of Example 1.

[0075] The test results are shown in Table 1.

[0076] Example 4

[0077] The difference from Example 2 is that 7 parts of bentonite are added;

[0078] Except for the above differences, other conditions of Example 4 are the same as those of Example 1.

[0079] The test results are shown in Table 1.

[0080] Example 5

[0081] The difference from Example 1 is that 7 parts of bentonite are added;

[0082] Except for the above differences, other conditions of Example 5 are the same as those of Example 1.

[0083] The test results are shown in Table 1.

[0084] Example 6

[0085] The difference from Example 1 is that the composition of the anti-collapse agent is different;

[0086] The anti-slump agent is prepared by adding 1.5 parts of ultrafine calcium carbonate (1200 mesh) and 1.5 parts of ultrafine calcium carbonate (2500 mesh), 1.5 parts of sulfonated asphalt powder, 2 parts of polypropylene fiber, 2 parts of mica and other solids, and mixing with 1.5 parts of emulsified asphalt liquid and 1.5 parts of nano silicon dioxide, and stirring at 1200 rpm for 5 minutes to obtain the anti-slump agent;

[0087] Except for the above differences, other conditions of Example 6 are the same as those of Example 1.

[0088] The test results are shown in Table 1.

[0089] Example 7

[0090] The difference from Example 1 is that 0.1 parts of soda ash, 4 parts of sulfonated phenolic resin as a fluid loss reducer, 4 parts of lignite resin as a fluid loss reducer, 2 parts of polyanionic cellulose as a fluid loss reducer, 8 parts of potassium chloride, and 2 parts of polyamine are added;

[0091] Except for the above differences, other conditions of Example 7 are the same as those of Example 1.

[0092] The test results are shown in Table 1.

[0093] Example 8

[0094] The difference from Example 1 is that the amount of asphalt in the anti-collapse agent is different, which is 2 parts of sulfonated asphalt powder and 5 parts of emulsified asphalt liquid; the mass ratio of API barite to submicron barite in the weighting agent is different, which is 4:1;

[0095] Except for the above differences, other conditions of Example 8 are the same as those of Example 1.

[0096] The test results are shown in Table 1.

[0097] Example 9

[0098] The difference from Example 1 is that the stirring rate is 1000 r / min, and each component is added in sequence and stirred for 8 minutes;

[0099] Except for the above differences, other conditions of Example 9 are the same as those of Example 1.

[0100] The test results are shown in Table 1.

[0101] Comparative Example 1

[0102] The difference from Example 1 is that no anti-collapse agent is added;

[0103] Except for the above differences, other conditions of Comparative Example 1 are the same as those of Example 1.

[0104] The test results are shown in Table 1.

[0105] Comparative Example 2

[0106] The difference from Example 2 is that different anti-collapse agents are added;

[0107] The anti-collapse agent added is specifically: 3 parts of ultrafine calcium carbonate (200-400 mesh), 3 parts of sulfonated asphalt powder, and 3 parts of emulsified asphalt liquid are mixed together and stirred at 1200 rpm for 5 minutes to prepare the anti-collapse agent;

[0108] Except for the above differences, other conditions of Comparative Example 2 are the same as those of Example 2.

[0109] The test results are shown in Table 1.

[0110] Table 1 Performance test experiments of different ultra-deep well high-temperature and high-density water-based drilling fluid formulas

[0111]

[0112] The lower the high temperature and high pressure filtration loss, the smaller the mud cake thickness and the better the anti-collapse effect.

[0113] From the performance test results in Table 1, we can see that:

[0114] (1) In Examples 1 to 9, by adjusting the drilling fluid density and the amount of additives added, a set of fracture zone wellbore stabilization drilling fluid system was established for the fault zone karst structure of the Shunbei Oil and Gas Field, objectively and truly reflecting the influence of different factors on the drilling fluid performance when drilling in an ultra-deep environment.

[0115] (2) The drilling fluids prepared in Examples 1 to 9 have a density between 1.6 and 2.0 g / cm 3 The high temperature and high pressure filtration loss is between 10.4 and 13.4 mL, and the mud cake thickness is between 1.3 and 2.7 mm, indicating that in the ultra-deep wellbore environment of the broken zone formation, the drilling fluid system can achieve a high temperature of 160 ° C and a mud cake thickness of 1.6 to 2.0 g / cm 3 It can achieve strong suppression and sealing at low density, effectively and quickly carry rock while maintaining the stability of the well wall, helping to achieve safe, optimal and fast drilling.

[0116] (3) By comparing Examples 1 to 9 with Comparative Examples 1 to 2, it can be seen that the higher the amount of bentonite and anti-collapse agent added, the better the anti-collapse effect of the drilling fluid.

[0117] (4) By comparing Examples 1 to 9 with Comparative Examples 1 to 2, it can be seen that the anti-collapse effect of the anti-collapse agent of the present invention in the drilling fluid is better than that of the existing anti-collapse agent, and the higher the proportion of submicron barite, the better the anti-collapse effect of the drilling fluid.

[0118] In summary, a drilling fluid for stabilizing the wellbore in a fractured zone of the present invention utilizes technical means such as "synergistic effect of anti-collapse agents with different particle sizes and different action mechanisms, high-temperature cross-linking of sulfonated drilling fluid system to improve system performance, and synergistic weighting of API barite and submicron barite" to achieve "strong suppression and strong blocking" of complex well sections in fractured formations in the fractured zone, ensuring effective rock carrying while maintaining wellbore stability, which has important practical significance for the realization of the large-scale oil and gas development strategy in the fractured zone of Shunbei Oil and Gas Field.

[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A drilling fluid comprising water, bentonite, a fluid loss reducer, an inhibitor, an anti-collapse agent, soda ash, caustic soda, a dispersant and a weighting agent; Taking water as 100 parts by weight, it comprises:

2. The drilling fluid according to claim 1, characterized in that: The fluid loss reducer is at least one of sulfonated phenolic resin SMP, polyanionic cellulose LV-PAC, sodium carboxymethyl cellulose Na-CMC, and lignite resin; and / or, The inhibitor is at least one of potassium chloride, polyamine, hydrolyzed polyacrylamide potassium salt, potassium humate, and polyol; and / or, The anti-collapse agent includes a well wall strengthening agent, asphalt, a micro-nano plugging agent, a fiber material, and a sheet-like flexible bridging material; and / or, The dispersant is at least one of sodium polyacrylate, tannin lye, and iron chromium lignin sulfonate; and / or, The weighting agent is at least one of API barite, submicron barite, limestone powder and hematite powder; preferably, it is a mixture of API barite and submicron barite, and more preferably, the mass ratio of API barite to submicron barite is (1.5-4):

1.

3. The drilling fluid according to claim 2, characterized in that: The anti-collapse agent comprises the following components:

4. The drilling fluid according to claim 3, characterized in that: The well wall strengthening agent is ultrafine rigid particles, preferably at least one of ultrafine calcium carbonate, elastic graphite, limestone, sulfur ore powder, and ultrafine calcium silicate, preferably ultrafine calcium carbonate; more preferably at least one of 200 mesh, 400 mesh, 800 mesh, 1200 mesh, and 2500 mesh in particle size; and / or, The asphalt is at least one of sulfonated asphalt, emulsified asphalt, modified sulfonated asphalt and mineral asphalt; and / or, preferably, a mixture of sulfonated asphalt and emulsified asphalt, more preferably, the mass ratio of sulfonated asphalt to emulsified asphalt is 1: (1-2.5); and / or, The micro-nano plugging agent is at least one of nano-silicon dioxide and nano-cement, and preferably has a median particle size of less than 1.0 μm; and / or, The fiber material is at least one of polypropylene fiber, carbon fiber, cotton fiber or wood fiber; and / or, The sheet-like flexible bridging material is at least one of mica, wood chips and celluloid.

5. The drilling fluid according to claim 1, characterized in that: The pH of the drilling fluid is 8 to 12, preferably 9.0 to 10.0; and / or, The drilling fluid density is 1.2 to 2.2 g / cm 3 , preferably 1.6 to 2.0 g / cm 3 .

6. A method for preparing a drilling fluid according to any one of claims 1 to 5, comprising: The bentonite is prehydrated first, and then mixed evenly with a fluid loss reducer, an inhibitor, an anti-collapse agent, caustic soda, a dispersant and a weighting agent to obtain the drilling fluid.

7. The method for preparing the drilling fluid according to claim 6, characterized in that: (1) prehydrating bentonite to obtain a prehydrated bentonite slurry; (2) Under stirring, the fluid loss reducer, inhibitor, anti-collapse agent, caustic soda, dispersant and weighting agent are sequentially added to the prehydrated bentonite slurry obtained in step (1) and mixed evenly.

8. The method for preparing a drilling fluid according to claim 5, wherein: Step (1), Under stirring, bentonite is added to water and mixed evenly, and then soda ash is added and mixed evenly to obtain a prehydrated bentonite slurry; preferably, The mixing temperature is 10 to 80°C, preferably 20 to 60°C; and / or, The stirring rate is 800 to 1600 r / min, preferably 1000 to 1200 r / min; and / or, The mixing time after adding bentonite is 3 to 10 minutes, preferably 5 to 8 minutes; and / or, The mixing time after adding soda ash is 3 to 10 minutes, preferably 5 to 8 minutes; and / or, Step (2), The stirring rate is 800 to 1600 r / min, preferably 1000 to 1200 r / min; and / or, Each component added in sequence should be stirred for 3 to 10 minutes, preferably 5 to 8 minutes.

9. A drilling fluid obtained by the preparation method according to any one of claims 6 to 8.

10. Use of the drilling fluid as claimed in any one of claims 1 to 5 and 9 in oil and gas drilling in fractured formations, preferably in drilling in ultra-deep formations in fractured zones or in abnormally high-pressure well sections.

Citation Information

Patent Citations

  • Deepwater high-density drilling fluid capable of resisting high temperature of 220 DEG C

    CN110819318A

  • Anti-collapse drilling fluid for coal seams, and preparation method thereof

    CN111117579A

  • Three-protection-function water-base drilling fluid system

    CN111574973A

Cited By

  • Sulfonated anti-sloughing drilling fluid and preparation method thereof

    CN120005580A

  • A sulfonated anti-collapse drilling fluid and its preparation method

    CN120005580B